A Neural Crest-specific Overexpression Mouse Model Reveals the Transcriptional Regulatory Effects of Dlx2 During Maxillary Process Development - Sun, Jian; Ha, NaYoung; Liu, Zhixu; Bian, Qian; Wang, Xudong (Frontiers in Physiology, 2022)
Craniofacial morphogenesis is a complex process that requires precise regulation of cell proliferation, migration, and differentiation. Perturbations of this process cause a series of craniofacial deformities. Dlx2 is a critical transcription factor that regulates the development of the first branchial arch. However, the transcriptional regulatory functions of Dlx2 during craniofacial development have been poorly understood due to the lack of animal models in which the Dlx2 level can be precisely modulated. In this study, we constructed a Rosa26 site-directed Dlx2 gene knock-in mouse model Rosa26CAG-LSL-Dlx2-3xFlag for conditionally overexpressing Dlx2. By breeding with wnt1cre mice, we obtained wnt1cre; Rosa26Dlx2/- mice, in which Dlx2 is overexpressed in neural crest lineage at approximately three times the endogenous level. The wnt1cre; Rosa26Dlx2/- mice exhibited consistent phenotypes that include cleft palate across generations and individual animals. Using this model, we demonstrated that Dlx2 caused cleft palate by affecting maxillary growth and uplift in the early-stage development of maxillary prominences. By performing bulk RNA-sequencing, we demonstrated that Dlx2 overexpression induced significant changes in many genes associated with critical developmental pathways. In summary, our novel mouse model provides a reliable and consistent system for investigating Dlx2 functions during development and for elucidating the gene regulatory networks underlying craniofacial development.